THE ASSOCIATION OF EATING BEHAVIORS ON OBESITY ADOLESCENT WITH THE ADEQUACY OF CARBOHYDRATE NUTRIENT IN PERGURUAN ISLAM AL ULUM TERPADU - Gultom, Ade CH.; Istian, Ria (JURNAL PENELITIAN SAINTIKA, 2016)
This study aims to (1) To identify the characteristics of the family (father and mother age, family size, father and mother education, father and mother occupation, family income), (2) To determine the obesity adolescent eating behavior, (3) To determine the adequacy carbohydrate nutrient on obesity adolescents, and (4) To determine the association eating behavior obesity with carbohydrate nutrient adequacy. The research was conducted in December 2014. The research location in SMA Islam AlUlum Terpadu. The sampling technique using purposive sampling method with criteria for students who has weight that categorized as obesity. The technique of collecting data is primary data which collected such as the family characteristics data including father and mother age, family size, father and mother education, fathers and mothers occupation, father and mother income. Eating behavior on obesity adoloescent data were collected through semi-frequency food method (food frequency). The adequacy of carbohydrate nutrients data was collected by using food recall 2 x 24 hours method. The analyzing data technique of family characteristics was descriptively. Eating behavior data was analyzed into good and less category. Adequacy of carbohydrate nutrient data was analyzed into good, moderate, less, and deficit. To see the association of eating behavior on obesity adolescent with adequate of carbohydrate nutrient was analyzed by using Spearman Correlation test.The research result showed that family characteristics seen from the father’s age average which is 48,48 years old, while the mother's age is about 44,45 years. The number of family members is about 6,09 people with middle family category. The average education level of father is 14,94 years (academic/university). Father's occupation are self-employed, entrepreneur, civil servants, military, police, employee, lecture and lawyer, while the mother’s occupation are housewife, self-employment, civil servant, entrepreneur, teacher, employee, insurance Agents and policewomen. The average of family income is Rp 10,524,424 for month. Whole of eating behavior on obesity adolescents includes to good category, that is 75.76 percent. Adequacy of carbohidrate nutrients mostly includes to good category, that is 87.88 percent. Spearman correlation test results showed that there is a significant relationship between eating behavior on obesity adolescents ( = 0.000, r = 0.815) with the adequacy of carbohydrate nutrient. This thing shows that if eating behavior getting better, so that the adequacy of carbohydrate nutrient too.